IMPROVEMENT OF WORK DISCIPLINE THROUGH MOTIVATION, COMPENSATION AND WORKING ENVIRONMENT : PENINGKATAN DISIPLIN KERJA MELALUI MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA - Encep Saefullah; Tabroni Tabroni (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This research aims to analyze the influence of motivation, compensation, and work environment on work discipline. Population and sample are employees with the State Civil Apparatus (ASN) status in the Office of Library and Archives Banten Province as many as 70 employees. The data collection method uses a questionnaire, and the analysis technique used is multiple regression. The results showed that 1) motivation has a positive and significant effect on work discipline. 2) compensation has a positive and significant effect on work discipline. 3) the work environment has a positive and significant effect on work discipline. 4) motivation, compensation and work environment have a positive and significant effect on work discipline